Increasing of communication research about vaccine in WoS publications - Estrella-Pacheco, Makarena (Revista Española de Comunicación en Salud, 2023)
Introduction: Research on vaccines, and their later application to society, created the necessity of communication strategies, taking also into account the fake-news propaganda. All these with the sole purpose of keeping the population informed about the treatments against COVID-19. This leads to the reaction of the academic community, which has investigated and explained how these phenomena are developing. Objectives: To analyze the reaction of communication research areas on this inoculation matter based on the increasing of paper publications and citations in indexed journals on the Web of Science (WoS). Methodology: Quantitative analysis of the number of publications and citations on the vaccine topic by using the topic category Communication on WoS. It has been studied for the last 12 years and three months (January 2010 to March 2022), by comparing the state-of-the-art of this area earlier and after the COVID-19 pandemic. Results: It is corroborated that in the years 2020, 2021 and the first trimester of 2022 the number of publications and citations about vaccines in communication journals has experienced exponential growth approximately. Conclusions: The academic community that published in indexed journal on the communication category have reacted to the appearance of vaccines and the communication phenomena related to them.